ANALISIS PENGENDALIAN INTERNAL DALAM SISTEM DAN PROSEDUR PENGGAJIAN PADA PT CENTRAL MITRA SEMESTA LAMONGAN - Marlyta, Irrena Dwi; Nasution, Ute Ch; Mulyati, Diana Juni (Jurnal Dinamika Administrasi Bisnis, 2019)
In the current era of globalization, in the business world, it requires an important aspect to advance a company, one of which is human resources. To get competent and qualified human resources, companies need to ensure the welfare of workers by giving them rights, namely salaries, as reciprocity for the services they have given to the company. In each activity has control over activities that are being and have been carried out. Likewise with the employee payroll system and procedures within the company. The application of an internal control system in the company is very necessary. This research was conducted to find out whether the internal control system in the payroll system and procedures in the company has been running effectively.The object examined is PT Central Mitra Semesta Lamongan which is engaged in replanting services. The method used is descriptive qualitative. Research results show that the payroll system and procedures of PT Central Mitra Semesta Lamongan in fulfilling the elements and objectives of internal control over the payroll system have not been effective, this is characterized by a lack of functions in the organizational structure within the company resulting in a doubling of duties in procedures for making payroll salary payment procedure. less effective recording of employee attendance time so that fraud occurs when calculating working hours and work hours.Keywords: Salaries, systems and procedures, internal control systems